69. Thirty Years of Distance Education: Personal Reflections - McKee, Terralyn (International Review of Research in Open and Distributed Learning, 2010)
This paper reflects on the evolving experience of modern distance education (DE) as a field of practice for professionals and as a medium for student access to education and training. The writer’s 30 years in the field, as both teacher and student, has coincided with the five-stage evolution of DE delivery defined by Taylor (1995-2010). The author considers the perceived identity crisis and diverse theoretical frameworks of the field since the 1980s as well as the need for new levels of change management that will enable the tools, technologies, and emerging systems of DE to create the flexibility, responsiveness, and networking that the students require and that the teachers need to learn.